Identification of a potential antimicrobial peptide derived from Haliotis midae haemocyanin - North, Jarid (Department of Molecular and Cell Biology, 2020)
Haliotis midae aquaculture within South Africa remains afflicted by infectious diseases. Understanding of how the abalone’s innate immune response functions is one of the greatest hindrances to assisting with the defence or detection of pathogenic attacks on farms. The multifunctional oxygen transporter haemocyanin was previously found to be upregulated in response to bacterial infection (Beltran 2015), indicating it may play a role in the defence response of Haliotis midae. The current knowledge regarding haemocyanin’s role in the abalone innate immune response is incomplete. A number of studies have been published that investigated haemocyanin’s potential as a broad spectrum antimicrobial peptide in many arthropod species. There has been only one study conducted in molluscs, which utilised synthetic peptides derived from a haemocyanin consensus sequence. In most organisms the haemocyanin protein is comprised of a string of eight roughly 50 kDa functional units (FU) annotated a-h. The current study determined the nucleotide sequence of the final four functional units on the C-terminal end of H. midae haemocyanin and examined the potential antimicrobial activity of the peptide product. The haliotisin coding sequence identified by Zhuang et al. (2015) was detected in FU-e of the H. midae haemocyanin and subcloned into an Escherichia coli expression vector for recombinant production of the peptide. This peptide showed some activity against Staphylococcus aureus and E. coli, suggesting it may function as an antimicrobial peptide. This study provides the first evidence that an antimicrobial peptide derived from the H. midae haemocyanin could be functioning as a component of the abalone innate immune response.